2013
DOI: 10.1007/s00439-013-1368-2
|View full text |Cite
|
Sign up to set email alerts
|

Replication of a GWAS signal in a Caucasian population implicates ADD3 in susceptibility to biliary atresia

Abstract: In the United States, biliary atresia (BA) is the most frequent indication for liver transplantation in pediatric patients. BA is a complex disease, with suspected environmental and genetic risk factors. A genome-wide association study in Chinese patients identified association to the 10q24.2 (hg18) genomic region. This signal was upstream of two genes, XPNPEP1 and ADD3, both expressed in intrahepatic bile ducts. We tested association to this region in 171 BA patients and 1,630 controls of European descent and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 63 publications
(67 citation statements)
references
References 27 publications
3
63
0
1
Order By: Relevance
“…Biliary atresia is not generally thought of as an inherited disease, although there are some lines of evidence to support the hypothesis that genetic factors contribute to disease susceptibility (Garcia-Barceló et al, 2010;Tang et al, 2016;Tsai et al, 2014). Our study has indicated that inhibiting the Cdk5-mediated pathway can generate phenotypes similar to those seen in biliary atresia patients.…”
Section: Discussionsupporting
confidence: 53%
“…Biliary atresia is not generally thought of as an inherited disease, although there are some lines of evidence to support the hypothesis that genetic factors contribute to disease susceptibility (Garcia-Barceló et al, 2010;Tang et al, 2016;Tsai et al, 2014). Our study has indicated that inhibiting the Cdk5-mediated pathway can generate phenotypes similar to those seen in biliary atresia patients.…”
Section: Discussionsupporting
confidence: 53%
“…One gene in the region of this SNP is adducin 3 ( ADD3) . A study in the United States analyzing this genetic region confirmed an association of ADD3 and BA [19]. ADD3 is expressed in hepatocytes and biliary epithelia, and is involved in the assembly of spectrin–actin membrane protein networks at sites of cell-to-cell contact.…”
Section: Theories Of Pathogenesismentioning
confidence: 89%
“…Some of the genes, such as forkhead box A2 ( FOXA2 ), have been linked to BA only in members of a single family . ADD3 was found in some single‐nucleotide polymorphism GWAS, and GPC1 was identified through CNV studies; disruption of either of these genes in zebrafish results in biliary defects . Preliminary data presented at the symposium on ongoing genetic studies using whole‐exome sequencing of BASM trios identified PKD1L1 variants, raising the potential that abnormal ciliary function contributes to disease susceptibility.…”
Section: Basic Researchmentioning
confidence: 99%